FLAVONOID PROFILE OF “AS-INFUSUM” AND ITS BIOLOGICAL ACTIVITY - Askarov, Ibrokhim Rakhimjonovich; Abdullaev, Shavkat Vokhidovich; Khaydarov, Eldorbek Rakhimjon o‘g‘li; Xasanbayevich, Qirg‘izbayev Xusniddin (Research Focus International Scientific Journal, 2026)
This study investigates the flavonoid composition of the “As-Infusum” plant- based infusion using high-performance liquid chromatography (HPLC). The results demonstrated that rutin (39.12 mg/g) is the predominant component, determining the antioxidant and cardioprotective properties of the infusion. Additionally, flavonoids such as dihydroquercetin rosavin, quercetin, and salidroside were identified, contributing to the biological activity and enhancing the pharmacological and nutraceutical potential of the infusion.